3D printing bionic structure composite material and preparation method thereof

Through direct ink writing 3D printing technology and bionic bollinger structure design, combined with carbon fiber orientation regulation, the problem of poor structural properties of existing epoxy resin-based composite materials has been solved, significantly improved its friction performance, and has important engineering application value.

CN119682211APending Publication Date: 2025-03-25TIANJIN POLYTECHNIC UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928641.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing resin-based composite materials formed by epoxy resins with glass fibers or natural fibers after 3D printing have good anti-friction and wear properties, but their poor structural properties limit their performance in engineering applications.

Method used

Through direct ink writing 3D printing technology, combining macroscopic structural design with microfiber alignment control, a bionic bollinger root structure is adopted, and the tribological properties of the composite material are optimized by adjusting the orientation of the carbon fiber.

Benefits of technology

The customized design of friction material structure is realized, which significantly improves the wear resistance and friction performance of composite materials, especially in environments with high loads or long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682211A_ABST
    Figure CN119682211A_ABST
Patent Text Reader

Abstract

The invention relates to a 3D printing bionic structure composite material and a preparation method thereof, and the tribological performance of the composite material is optimized by adopting a direct ink writing (DIW) 3D printing technology and combining carbon fiber surface modification and bionic bringed structure design. Firstly, through ultrasonic treatment, nitric acid modification and silane coupling agent modification, the interface cohesiveness of carbon fibers and an epoxy resin matrix is improved, and therefore the mechanical property of the material is enhanced. Then, the orientation of the carbon fibers and the structure of the composite material are accurately controlled through the 3D printing technology, and the composite material with the excellent friction performance is prepared. Compared with the prior art, the composite material disclosed by the invention is remarkably improved in the aspects of wear resistance, friction coefficient and the like, and is suitable for manufacturing high-performance parts in the fields of friction materials, aerospace, automobiles, machinery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of direct writing 3D printing, and in particular relates to a 3D printing bionic structure composite material and a preparation method thereof. Background Art

[0002] 3D printing technology is an additive manufacturing technology that integrates materials, geometric structures and computer technology. It has the advantages of high material utilization, low cost and short molding cycle, and can design complex geometric shapes. Composite materials are materials with high specific strength, high specific modulus and good designability. The preparation of 3D printed composite materials is a frontier direction of cross-research in the field of 3D printing manufacturing and composite materials technology. With the continuous development of 3D printing technology and composite materials, the combination of the two has brought significant impetus to manufacturing, environmental protection and scientific and technological innovation.

[0003] In recent years, epoxy resin has been widely used in many polymer composite materials. It is an important thermosetting material with significant strategic significance. It has attracted the attention of a wide range of scholars for its excellent bonding properties, high modulus, easy molding, heat resistance and chemical resistance. In the study of composite materials, epoxy resin is often used as a matrix material for further enhancement research and is widely used in manufacturing fields such as aerospace, aviation, wind power, nuclear power and high-speed railway. Therefore, it is also popular in 3D printing materials. However, the existing resin-based composite materials formed by epoxy resin and glass fiber or natural fiber have good anti-friction and wear properties after 3D printing, but their structure is poor, which limits their performance in engineering applications. For example, although patent CN114702784B enhances the compatibility of natural fibers and resins through alkali treatment, isocyanate modification and silane coupling agent modification, the interfacial bonding between natural fibers and epoxy resin may still not be as strong as some traditional reinforcement materials (such as glass fiber, carbon fiber). This may affect the overall mechanical properties of the composite material, especially in high-load or long-term use environments. Summary of the invention

[0004] In view of the above problems in the prior art, the present invention uses direct ink writing 3D printing technology for the first time, combines macroscopic structural design with microscopic fiber alignment control, breaks through the limitations of traditional manufacturing technology, and realizes customized design of friction material structure. The composite material prepared by direct ink writing 3D printing technology adopts a bionic Bouligand structure, and optimizes the tribological properties of the composite material by adjusting the carbon fiber orientation. The technology of the present invention has important engineering application value, especially in the field of tribology of epoxy resin-based composite materials, and can effectively optimize its manufacturing process and application performance.

[0005] In order to solve the above technical problems, the present invention provides a method for 3D printing a bionic structure composite material, which specifically comprises the following steps:

[0006] The carbon fiber is mixed with an ethanol solution, subjected to ultrasonic treatment, and then filtered, and the treated carbon fiber is dried to obtain a carbon fiber with a clean surface;

[0007] Under vacuum conditions, the treated carbon fiber, nitric acid and an organic solvent are mixed to perform a nitric acid modification reaction to obtain nitric acid-modified carbon fiber;

[0008] Under vacuum conditions, nitric acid-modified carbon fiber, a silane coupling agent and an organic solvent are mixed to perform silane coupling agent modification to obtain silane-nitric acid-modified carbon fiber;

[0009] Silane-nitric acid modified carbon fiber, epoxy resin, silicon dioxide and curing agent are mixed to obtain epoxy resin-based ink, wherein the mass percentage content of silane-nitric acid modified carbon fiber in epoxy resin is 2-6%.

[0010] Preferably, the mass ratio of carbon fiber to nitric acid is (1-4):(6-16).

[0011] Preferably, the mass ratio of carbon fiber to silane coupling agent is (1-4):(6-16).

[0012] Preferably, the mass ratio of carbon fiber, epoxy resin, silica and curing agent is (0.8-1.4):(8-12):(1-1.8):(0.6-1.3).

[0013] Preferably, the organic solvent is styrene or N-dimethylformamide (DMF).

[0014] Preferably, the insulation temperature of the nitric acid modification reaction is 80° C. to 100° C., and the insulation time is 2 to 4 hours.

[0015] Preferably, the insulation temperature of the silane coupling agent modification reaction is 35° C. to 70° C., and the insulation time is 2 to 4 hours.

[0016] Preferably, the mass percentage of the ethanol solution is 70-100%, and the mass ratio of the carbon fiber to the ethanol solution is (0.8-1.4):(2-6).

[0017] Preferably, the average length of the carbon fiber is 200-350 μm, and the aspect ratio is (10-30):1.

[0018] Preferably, the ultrasonic power of the ultrasonic treatment is 100-300W.

[0019] Preferably, the ultrasonic treatment time is 10 to 30 minutes.

[0020] Preferably, the interlayer angle of the 3D printed bionic structure is 0° to 50°.

[0021] Preferably, the 3D printing technology is direct ink writing (DIW).

[0022] Preferably, the extrusion pressure of the 3D printer is 150-300 Pa.

[0023] Preferably, the inner diameter of the needle of the 3D printer is 260-540 μm.

[0024] Preferably, the printing speed of the 3D printer is 10-20 mm / s.

[0025] Preferably, the printing layer height of the 3D printer is 300-400 μm.

[0026] Preferably, the printing pitch of the 3D printer is 200-300 μm.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention realizes customized design of friction materials by adopting a bionic Boulingand structure and combining it with the orientation control of carbon fiber. The Boulingand structure usually has good mechanical properties and tribological properties, so it can effectively improve the wear resistance and friction performance of composite materials. Through direct ink writing (DIW) 3D printing technology, the material structure can be accurately controlled, especially in the directional arrangement of microscopic fibers and the design of macroscopic structure, thereby improving the tribological performance of composite materials.

[0029] The composite of carbon fiber, silane coupling agent, epoxy resin and other materials is used, and the carbon fiber is modified by nitric acid and silane coupling agent to improve the interfacial adhesion between the carbon fiber and the resin matrix. This modification process improves the mechanical properties and durability of the material, especially the stability under high load and long-term use environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic diagram of a direct writing 3D printing device;

[0031] Figure 2 This is a schematic diagram of the Bollinger structure;

[0032] Figure 3 A comparison chart of the friction coefficients of composite materials products in the embodiments of the present invention; DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the specific implementation of the present invention is further described below in conjunction with the accompanying drawings and specific implementation examples, but the implementation methods of the present invention are not limited thereto.

[0034] Example 1

[0035] Two parts of carbon fiber were added to nine parts of 90 wt% ethanol solution, and ultrasonically treated at an ultrasonic power of 200 W for 20 minutes, and then filtered and dried to obtain carbon fiber without impurities;

[0036] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0037] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0038] The parameters of the above 3D printer are set as follows: extrusion pressure is 200Pa, needle inner diameter is 360μm, printing speed is 12mm / s, printing layer height is 340μm, and printing spacing is 240μm.

[0039] The interlayer angle of the 3D printed bionic structural composite material is 0°.

[0040] Example 2

[0041] Two parts of carbon fiber were added to nine parts of 90 wt% ethanol solution, and ultrasonically treated at an ultrasonic power of 200 W for 20 minutes, and then filtered and dried to obtain carbon fiber without impurities;

[0042] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0043] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0044] The parameters of the above 3D printer are set as follows: extrusion pressure is 200Pa, needle inner diameter is 360μm, printing speed is 12mm / s, printing layer height is 340μm, and printing spacing is 240μm.

[0045] The interlayer angle of the 3D printed bionic structural composite material is 15°.

[0046] Example 3

[0047] Two parts of carbon fiber were added to nine parts of 90 wt% ethanol solution, and ultrasonically treated at an ultrasonic power of 200 W for 20 minutes, and then filtered and dried to obtain carbon fiber without impurities;

[0048] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0049] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0050] The parameters of the above 3D printer are set as follows: extrusion pressure is 200Pa, needle inner diameter is 360μm, printing speed is 12mm / s, printing layer height is 340μm, and printing spacing is 240μm.

[0051] The interlayer angle of the 3D printed bionic structural composite material is 30°.

[0052] Example 4

[0053] Two parts of carbon fiber were added to nine parts of 90 wt% ethanol solution, and ultrasonically treated at an ultrasonic power of 200 W for 20 minutes, and then filtered and dried to obtain carbon fiber without impurities;

[0054] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0055] The carbon fiber and 6 parts of nitric acid were placed in a beaker, and 100 parts of DMF solvent were added. Under vacuum conditions, the reaction temperature was set to 90°C, and the nitric acid modification reaction was carried out for 2.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 12 parts of silane coupling agent were added, and the silane coupling agent modification reaction was continued under vacuum. After filtration and drying, silane-nitric acid modified carbon fiber was obtained.

[0056] The parameters of the above 3D printer are set as follows: extrusion pressure is 200Pa, needle inner diameter is 360μm, printing speed is 12mm / s, printing layer height is 340μm, and printing spacing is 240μm.

[0057] The interlayer angle of the 3D printed bionic structural composite material is 45°.

[0058] The friction performance of the carbon fiber reinforced epoxy resin composites printed in Example 1, Example 2, Example 3 and Example 4 was tested. The test results are shown in Table 1. Figure 3 As shown in Table 1 and Figure 3 It can be seen that the composite material with a structure having an interlayer angle of 15° prepared by the preparation method provided by the present invention exhibits more excellent friction performance.

[0059] Table 1 Friction performance test results of products printed in Example 1, Example 2, Example 3 and Example 4

[0060] Serial number Average friction coefficient <![CDATA[Wear rate / mm 3 / (N m)]]> Example 1 0.35 <![CDATA[2.3×10 -5 ]]> Example 2 0.29 <![CDATA[2.1×10 -5 ]]> Example 3 0.41 <![CDATA[3.4×10 -5 ]]> Example 4 0.45 <![CDATA[3.7×10 -5 ]]>

[0061] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a 3D printed bionic structure composite material, characterized in that: The following steps are involved: 1) Under vacuum conditions, the fiber is mixed with nitric acid and an organic solvent to perform a nitric acid modification reaction to obtain nitric acid-modified carbon fiber; 2) under vacuum conditions, mixing the nitric acid-modified carbon fiber with a silane coupling agent and an organic solvent to perform silane coupling agent modification to obtain a silane-nitric acid-modified carbon fiber; 3) mixing silane-nitric acid modified carbon fiber, epoxy resin, silicon dioxide and curing agent to obtain epoxy resin-based ink; 4) Printing the epoxy resin-based ink into a composite material with a bionic Bollinger structure through direct ink writing (DIW) 3D printing technology.

2. The method for preparing the 3D printed bionic structure composite material according to claim 1, characterized in that: The mass ratio of carbon fiber to nitric acid is (1-4):(6-16).

3. The method for preparing the 3D printed bionic structure composite material according to claim 1, characterized in that: The mass ratio of carbon fiber to silane coupling agent is (1-4): (6-16).

4. The method for preparing the 3D printed bionic structure composite material according to claim 1, characterized in that: The mass ratio of carbon fiber, epoxy resin, silicon dioxide and curing agent is (0.8-1.4):(8-12):(1-1.8):(0.6-1.3).

5. The method according to claim 1, characterized in that The organic solvent is styrene or N-dimethylformamide (DMF).

6. The method for preparing the 3D printed bionic structure composite material according to claim 1, characterized in that: The insulation temperature of the nitric acid modification reaction is 80°C to 100°C, and the insulation time is 2 to 4 hours; the insulation temperature of the silane coupling agent modification reaction is 35°C to 70°C, and the insulation time is 2 to 4 hours.

7. The method for preparing a 3D printed bionic structure composite material according to claim 1, characterized in that: The interlayer angle of 3D printing is 0°~50°.

8. The method for preparing a 3D printed bionic structure composite material according to claim 1, characterized in that: The 3D printing technology is direct ink writing (DIW).

9. The method for preparing a 3D printed bionic structure composite material according to claim 1, characterized in that: The extrusion pressure of the 3D printer is 150-300 Pa, the inner diameter of the needle is 260-540 μm, the printing speed is 10-20 mm / s, the printing layer height is 300-400 μm, and the printing spacing is 200-300 μm.

10. A 3D printed bionic structural composite material, characterized in that: The preparation method is as described in any one of claims 1 to 9.